2021
DOI: 10.1094/pbiomes-12-20-0091-r
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Responses of Vitis aestivalis ‘Norton’ and Vitis vinifera ‘Kishmish Vatkana’ to Seven Viruses Revealed by Small RNA Sequencing

Abstract: Grapevines are frequently infected by multiple viruses. Our previous study showed that ‘Norton’ grapevine (Vitis aestivalis) is resistant to grapevine vein clearing virus, a DNA virus in the family Caulimoviridae. To study the reaction of ‘Norton’ to RNA viruses, we transferred seven RNA viruses to ‘Norton’ from ‘Kishmish Vatkana’ (‘KV’) (Vitis vinifera) via graft-transmission. We profiled viral small RNAs (vsRNAs) of the seven viruses and compared viral titers in ‘Norton’ and ‘KV’. Total vsRNAs of grapevine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In either case, the accumulation of viral small RNAs of grapevine leafroll viruses 1, 2, and 3 in Norton was lower than in Kishmish vatkana. A RT-PCR analysis of infected vines indicated that GLRaV-1 was undetectable in Norton, and confirmed that GLRaV-2 and 3GLRaV-3 were less abundant in Norton than Kishmish vatkana (Howard et al 2021). The authors concluded that Norton suppresses infections by GLRaV-1, GLRaV-2, and GLRaV-3.…”
Section: Impact Of Gvcv On Vine Health and Berry Qualitymentioning
confidence: 85%
See 2 more Smart Citations
“…In either case, the accumulation of viral small RNAs of grapevine leafroll viruses 1, 2, and 3 in Norton was lower than in Kishmish vatkana. A RT-PCR analysis of infected vines indicated that GLRaV-1 was undetectable in Norton, and confirmed that GLRaV-2 and 3GLRaV-3 were less abundant in Norton than Kishmish vatkana (Howard et al 2021). The authors concluded that Norton suppresses infections by GLRaV-1, GLRaV-2, and GLRaV-3.…”
Section: Impact Of Gvcv On Vine Health and Berry Qualitymentioning
confidence: 85%
“…Between the screens of Norton for GVCV and the graft transmission studies, the authors concluded that Norton is resistant to GVCV. Howard et al (2021) compared the small RNAs that accumulated in Norton and the V. vinifera cultivar 'Kishmish Vatkana. The Kishmish vatkana cultivar in this study was infected with seven viruses.…”
Section: Impact Of Gvcv On Vine Health and Berry Qualitymentioning
confidence: 99%
See 1 more Smart Citation